A critical analysis of the agreement establishing a framework for an economic partnership agreement between the East African community partner states on one part and the European community and its member states on the other part : the most favoured nation clause - A Ugandan perspective - Bradlow, Daniel David (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2010.